Characteristic Making of Ba0.4Sr0.6TiO3 Thin Film Nanoparticles - Dewi, Rahmi; Krisman, Krisman; Zuhdi, Zuhdi; Rini, Ari Sulistyo; Hussains, Tengkusaidluqman (Trends in Sciences, 2022)
Presently, the research on thin films is essentially useful in the world of science and technology. Therefore, this study aims to explore Barium Strontium Titanate (BST) as the basis in the making of dynamic random access memory (DRAM). This DRAM technology produces small cells that have faster operations, lower energy, longer data storage period, and are found to havemade up of Barium Strontium Titanate nanoparticles (Ba0.4Sr0.6TiO3; BST). BST applications in the form of capacitors can be used as gas sensors, temperature sensors, microwave phase shifters, tunable filters, oscillators, infrared sensors, etc.The main component of BST was showed by the sol-gel method, and the device structure constituted of Si/SiO2/RuO2/TiO2 /Ba0.4Sr0.6TiO3/Al. All the samples were annealed at 400, 450, 500, 550, 600, 650 and 700 ℃ for 60 min. The sample was annealed to see the crystalline structure of the sample.The sol gel method was chosen in the process of making thin films of Ba0.4Sr0.6TiO3 (BST) because this method was easier and cheaper than other techniques. The thin film was characterized by optical and electrical properties. The results showed that a rise in the annealing temperature increased the crystalline, grain size, thickness and surface roughness of the sample. The characterization was carried out on the device structure (Si/SiO2/RuO2/TiO2/Ba0.4Sr0.6TiO3/Al) in order to examine the optical and electrical properties, including the current density and the dielectric features. At the annealing temperature of 700 ℃, the device showed the best value, with the absorption peak at the wavelength of 688 nm. And also, with the dielectric constant (εr) of 2,500, capacitance (C) of 22.10 nF, dense alternating current (ρau) of 2.54×104 Ω.m, conductance (σau) of 1.20×10-2 1/Ω.m, and current density of 9.85×10 -5 A.cm-2 at 0.5 V. The results of characterization of this capacitor are very good to be used as an infrared sensor. HIGHLIGHTS The explore Barium Strontium Titanate (BST) as the basis in the making of dynamic random access memory (DRAM) BST applications in the form of capacitors can be used as gas sensors, temperature sensors, microwave phase shifters, tunable filters, oscillators, infrared sensors, etc. The results showed that a rise in the annealing temperature increased the crystalline, grain size, thickness and surface roughness of the sample GRAPHICAL ABSTRACT